2016
DOI: 10.3345/kjp.2016.59.7.285
|View full text |Cite
|
Sign up to set email alerts
|

White matter injury following rotavirus infection in neonates: new aspects to a forgotten entity, 'fifth day fits'?

Abstract: That rotavirus infection can cause neurological symptoms in young children has been well established. However, it is surprising why rotavirus infection has been overlooked as a cause of neonatal seizures for many years, despite significant research interest in neonatal rotavirus infection. Neonates are the age group most vulnerable to seizures, which are typically attributed to a wide range of causes. By contrast, because rotavirus infection is usually asymptomatic, it has been difficult to identify an associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The characteristic white matter injury in newborns described here is not specific to encephalopathy associated with rotavirus infection. 7,23 White matter damage has also been observed in neonatal enterovirus and parechovirus encephalitis. 7,[23][24][25][26] The pathogenesis of white matter damage in viral infections is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic white matter injury in newborns described here is not specific to encephalopathy associated with rotavirus infection. 7,23 White matter damage has also been observed in neonatal enterovirus and parechovirus encephalitis. 7,[23][24][25][26] The pathogenesis of white matter damage in viral infections is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…7,23 White matter damage has also been observed in neonatal enterovirus and parechovirus encephalitis. 7,[23][24][25][26] The pathogenesis of white matter damage in viral infections is uncertain. Previous studies have suggested that white matter injury in newborns is related to a vulnerability of specific developmentally regulated cells, premyelinating oligodendrocytes, which are prevalent in white matter and are highly vulnerable to systemic infection or inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During infancy, the concomitant presence of febrile encephalopathy and gastroenteritis should raise the suspicion of rotavirus infection. The classical neuroimaging findings are ‘subtle or no change in T1 and T2 weighted sequences, but marked symmetric diffusion restriction in periventricular white matter, corpus callosum or thalamus’ 4. This pattern of white matter injury can be seen in parecho and enterovirus encephalopathy as well but, overtly restricting signals on diffusion sequences with no/subtle changes on conventional T1 and T2 weighted spin echo sequences is quite specific for rotavirus encephalopathy and gives an edge over the other two differentials 4.…”
Section: Descriptionmentioning
confidence: 99%
“…[1][2][3] The pattern of WMI is evident on diffusion-weighted images as symmetrical restricted diffusion in the periventricular white matter and along entire fiber tracts, including the corpus callosum. 1,4 The high positive rate of rotavirus infection in neonatal seizures with WMI [1][2][3] suggests that these two features are linked. For this hypothesis to be widely accepted, further studies are needed to elucidate the mechanisms of this phenomenon as well as the causal relationship.…”
Section: Introductionmentioning
confidence: 99%